The Scottish Parliament Election 2016: Another Momentous Event but Dull Campaign. Issue 3 (August 2016) - Cairney, Paul
Abstract : The Scottish Parliament election in 2016 produced two surprising results: it represents a reversal of SNP/ Labour party fortunes so complete that we now take it for granted, but the SNP did not achieve a widely-expected majority; and, the huge surge of support for the Scottish Conservatives was enough to make it (easily) the second largest party. A mistaken sense of inevitability of the result – another SNP majority – helped produce a dull campaign and keep alive the prospect of a second referendum on Scottish independence. This article has four main sections: putting the 2016 election in recent historical context; considering the implications of consistently high SNP support on the constitution; highlighting key issues in the election campaign; and, examining the SNP's policy agenda from 2016.